(untitled) (Contemporary Journal of Social Science Review, 2025)
The present study was conducted to analyze the impact of Premenstrual Syndrome, Psychological Distress, Self-control, and Social Connectedness on the mental health and academic achievements of college students in Shahdara, Lahore, Pakistan, highlighting the interconnected factors shaping their overall well-being and educational success. A total 300 female students as participants were selected from different colleges in Shahdara through purposive sampling. Multiple Regressions Analysis (Path Analysis) was applied to find the predictive relationship of demographic variables through the utilization of IBM SPSS for analysis. Standardized assessment tools in Urdu were utilized for this study, including the Premenstrual Symptoms Screening Tool (PSST) by Steiner et al. (2011), the Social Connectedness Scale by Erin York Cornwell (2009), the Self-Control Scale developed by Tangney, Baumeister, and Boone (2004), the Psychological Distress Scale by Kessler and Mroczek (1992). These tools were carefully selected to ensure cultural relevance and linguistic accuracy. A list of demographic variables with inform consent was taken for data collection permission was sought out from colleges. The results supported the hypothesis. The findings revealed that psychological distress, self-control, and social connectedness are predictors of PMS. Additionally, PMS was found to significantly influence psychological distress and self-control, while negatively impacting social connectedness among college students. The study concludes that premenstrual syndrome significantly influences psychological distress and self-control, while having a negative impact on social Connectedness among college students.